Determining the feasibility of implementing an ecological brick composed of PET and ash from the establishment of sale grilled chickens in the context of Tacna - Peru - Apaza Atencio, José Antonio (2021)
This research was developed in the city of Tacna, Peru, at an altitude of 564 m.a.s.l., with temperatures that varied from 12 ° C to 26 ° C. The purpose was to determine the economic and environmental feasibility of the use of ecological bricks (PET plastic compounds, ash from the establishment of sale of grilled chickens, sand and cement) for constructions, trying to provide an alternative solution parallel to the problem of atmospheric pollution caused by the brickyards and the abundance of solid waste in Tacna. Initially, 7 brick samples were manufactured with the mentioned components at different concentrations. These were subjected to tests for compressive strength, water absorption and heat transfer. Finally, an optimization was carried out, obtaining as ideal proportions: 50% cement, 25% PET plastic, 20% sand and 5% ash for the manufacture of ecological bricks, which complied with the Peruvian Technical Regulations currently required.